2005
DOI: 10.1128/aem.71.7.3668-3673.2005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fluid Shear and Microbubbles on Bacterial Detachment from a Surface

Abstract: Prevention of microbial adhesion and detachment of adhering microorganisms from surfaces is important in many environmental, industrial, and medical applications. Fluid shear is an obvious parameter for stimulating microbial detachment from surfaces, but recently it has been pointed out that a passing air-liquid interface also has potential in stimulating microbial detachment. In the present study, the ability of microbubbles to stimulate detachment of bacterial strains from a glass surface is compared with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 20 publications
1
69
0
Order By: Relevance
“…Consequently, the recycle liquid velocity can be varied over wide margins to gain control over the biofilm thickness. A background analysis referring to such flow procedure has been published recently [21].…”
Section: Effect Of Gas and Liquid Superficialmentioning
confidence: 99%
“…Consequently, the recycle liquid velocity can be varied over wide margins to gain control over the biofilm thickness. A background analysis referring to such flow procedure has been published recently [21].…”
Section: Effect Of Gas and Liquid Superficialmentioning
confidence: 99%
“…Fluid shear stress is an alternative mechanical approach for controlling biofilm build-up (Stewart, 2012). Previous studies have demonstrated that if sufficiently high fluid shear stress can be generated, this alone can stimulate biofilm detachment (Rutter and Vincent, 1988;Hope et al, 2003;Sharma et al, 2005a;Paramonova et al, 2009). High-velocity water droplets (Cense et al, 2006) and entrained air bubbles (Parini et al, 2005;Sharma et al, 2005b) have also been shown to be able to remove bacteria and biofilms from surfaces utilizing the additional effect of generating a "surface-tension force" away from the surface by the passage of an air/water interface (Gómez-Suárez et al, 2001).…”
mentioning
confidence: 99%
“…This indicates that microbubbled water has the effect on the tooth surface in a clinical situation. A previous study also showed that microbubbles were very effective to remove S. oralis from the glass plate [19][20] . Therefore the microbubbled water has the potential to prevent dental caries in the mouth of orthodontic patients.…”
Section: Discussionmentioning
confidence: 86%
“…The detachment of biofilm from the brachet by micro-bubbled water possibly depends on interface velocity, which is generated at gas-water interface 20) . Micro-bubbled water activates the hydrodynamic shear and surface tension forces, which causes the detachment of the biofilm from the orthodontic bracket.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation